Comportamento de argamassas industrializadas de assentamento submetidas a altas temperaturas - Zegarra, Rolando Ruben Chavez (2018)
This study investigates the behavior of industrialized mortar under high temperature conditions, analyzing the flexural tensile strength and axial compression strength. In order to carry out this research, three groups of industrialized mortars with nominal strengths of 6 MPa, 8 MPa and 12 MPa of the FIDA brand were subjected to temperatures of 100 ° C, 200 ° C, 300 ° C, 400 ° C, 500 ° C, 600 ° C, 700 ° C, 800 ° C and 900 ° C inside an electric oven for a period of 4 hours. The mortars were molded in test specimens following Brazilian Standard NBR 13276. For each exposure temperature, 18 specimens were molded to expose the temperatures mentioned, with test ages of 28 and 91 days. The 18 specimens were distributed as follows: 6 6 MPa specimens, 6 8 MPa specimens and 6 specimens of 12 Mpa, resulting in 198 specimens at various exposure temperatures. Samples with a 28-day and 91-day assay were placed at a constant temperature of 25 ° C in the Civil Construction Materials Laboratory of the Federal University of Santa Maria before being placed in the electric oven. After the test ages, the test specimens were subjected to the mentioned exposure temperatures, within an electric oven, for a period of 4 hours. The samples were cooled to room temperature and subjected to tensile fracture and axial compression tests, following Brazilian Standard NBR 13279. The results showed a decrease in tensile strength in flexion and axial compressive strength. Samples that were submitted to temperatures of 100 ° C, 200 ° C, 300 ° C, 400 ° C, 500 ° C and 600 ° C, decreased their resistance but maintained their structural integrity. The specimens subjected to temperatures of 700 ° C, 800 ° C and 900 ° C, after being cooled to room temperature for more than 24 hours, crumbled into powder. These samples were subjected to X-ray fluorescence spectrometry tests determining to what proportion in terms of oxides are within the mortars. For the X-ray diffraction, samples were submitted to ambient temperature, 200 ° C, 600 ° C and 900 ° C, observing that there were phase changes in the crystal structure of the oxides, due to the stress in the mortars when subjected to high temperatures, maintaining its chemical composition up to 900 ºC.